4 years old forever. (1st December 2016) - Herperger, Colin
An inquisitive sense of play begins to foster a curiosity that can grow and extend itself throughout a lifetime. This article looks at how drawing three-dimensionally with reflected light allows an opportunity for drawing to be constructed at the same speed as imagination occurs within one's mind. The opportunity of the drawing method leads to a range of interpretive potentials developed through two design research projects including a chandelier projection device and the architecture of a kindergarten. The research allows for the contribution of various instantaneous imaginations to contaminate the drawing process without the necessity of completely making sense at the time of the idea's conception. In order to foster such a delight for inventive play through drawing out one's imagination, the construction of a dysfunctional logic is developed as a sort of rule set to allow the growth of confidence within uncertain methods that hold an intuitive trust. Spatial invention through drawing leads to a range of physical models and constructions that seek to enjoy the translation of what is perceived within the reflected light drawings into physical realities. The intention of the research is to embrace this role of curious play and encourage its potential for a more engaged existence. This is undertaken by actively partaking in the process of design through making while simultaneously encouraging misbehaviour and the pleasure of uncertain discovery. The work trusts that the projects may develop as a number of diverse yet collaborative pieces that feel no responsibility to appear as a cohesive whole. An attitude of inventiveness sets up a curiosity to learn to see more in the world than what is obviously presented. Once we have begun to find such a world, how can we start to play with it?